2016
DOI: 10.5935/0104-7795.20160020
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic physical therapy in the treatment of a child with merosin-deficient congenital muscular dystrophy: case report

Abstract: This case report describes an aquatic therapy program for a child with Merosin-Deficient Congenital Muscular Dystrophy. Objective: This study sought to investigate the effect of aquatic physical therapy on the speed and the rate of energy expenditure while moving around on a flat surface, in addition to the functional reach of the upper limbs suffering from the proximal weakness that affects these patients seeking greater independence. Methods: The Motor Function Measurement (MFM) and the Functional Reach Test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Regarding postural control, studies have presented variables such as measuring range of motion 29 with goniometer, muscle strength with dynamometer 30 , and muscle activation with electromyography equipment 28 . Functional performance was analyzed mainly by Egen Most of the study participants had DMD, aged between 5 and 22 years old; in two studies, participants had limb-girdle muscular dystrophy 23,29 and one study presented congenital dystrophy 28 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Regarding postural control, studies have presented variables such as measuring range of motion 29 with goniometer, muscle strength with dynamometer 30 , and muscle activation with electromyography equipment 28 . Functional performance was analyzed mainly by Egen Most of the study participants had DMD, aged between 5 and 22 years old; in two studies, participants had limb-girdle muscular dystrophy 23,29 and one study presented congenital dystrophy 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Regarding postural control, studies have presented variables such as measuring range of motion 29 with goniometer, muscle strength with dynamometer 30 , and muscle activation with electromyography equipment 28 . Functional performance was analyzed mainly by Egen Most of the study participants had DMD, aged between 5 and 22 years old; in two studies, participants had limb-girdle muscular dystrophy 23,29 and one study presented congenital dystrophy 28 . Eight studies reported that individuals performed associated therapies, such as motor physical therapy 6,13,22,[27][28][29]31 , respiratory physical therapy 22,27 , occupational therapy 22,28 , home exercises 30 and adapted sports 31 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations